In silico study of the effectiveness of 16S rRNA gene as a universal genetic marker to identify closely related burkholderia spp. in panicle blight of rice / Nur Alifah Ilyana Mohamad Naim ...[et al.] - Mohamad Naim, Nur Alifah Ilyana; Tajul Anuar, Nabihah Raihanah; Ahmad, Lyena Watty Zuraine; Kambol, Roziah; Syed Mohamad, Sharifah Aminah; Aris, Farizan; Zakaria, Nurul Aili; Mohamed Yunus, Norfatimah (Universiti Teknologi MARA, 2022)
The 16S rRNA gene is a housekeeping genetic marker that is available in almost all bacterial species and it is used in bacterial phylogeny and taxonomy studies. In many studies, the 16S rRNA gene is used in identification of certain bacterial species. Being a less conserved genetic marker, certain studies found it is a useful tool to infer the genome-wide similarity levels among the closely related prokaryotic organisms. Thus, this study aimed to compare the variation in the 16S rRNA partial region of Burkholderia spp. that infect the panicle of rice from eight different geographical areas. 58 sequences with total of 688 base pairs (bp) of 16S rRNA gene in B. glumae and B. gladioli were retrieved from public database based on several countries namely United State, Panama, Ecuador, Thailand, China, India, Korea and Malaysia. Then, the data sequences were analysed and validated using MEGAX and ABGD software respectively. The result of phylogenetic tree confirmed that B. glumae and B. gladioli were species that present in the panicle blight of rice. However, Data Analysis in Molecular Biology and Evolution (DAMBE) and Automatic Barcode Gap Discovery (ABGD) software were not able to detect substitution saturation and divergence between B. glumae and B. gladioli respectively based on the 58 sequences of the 16S rRNA partial region. Hence, it proves that 16S rRNA gene is an ineffective genetic marker to be used to differentiate the closely related species of bacteria from similar genus.